Analisis Pengaruh Variasi Elektrolit H2SO4, KOH, dan Na2SO4 terhadap Kinerja Elektrokimia Superkapasitor berbasis Biomassa Kulit Kakao - Exaudi Pratama Rajagukguk; Widi Mulia Nasution; Mulda Muldarisnur; Yuli Yetri (Jurnal Fisika Unand, 2024)
Utilization of cocoa pod waste (Theobroma cacao) as a supercapacitor carbon electrode through electrolyte optimisation was successfully conducted with 0.5M KOH chemical activator. Carbon production starts with slicing cocoa pods, sun drying, pre-carbonisation, crushing of carbon particles with mortar and ball milling, and particle size uniformity using a sieve. The obtained particle powder was chemically activated with 0.5M KOH, coin-molded into of carbon monolith and finished with integrated pyrolysis. Samples were subjected to one-stage integrated pyrolysis by carbonisation from room temperature to 600˚ C in an N2 gas environment, followed by physical activation to 700˚ C in a CO2 gas environment. Testing the electrochemical properties of carbon electrodes based on different types of electrolytes (H2SO4, KOH, and Na2SO4) IM using cyclic voltammetry (CV) and galvanostatic charge discharge (GCD) methods. The sample provided with H2SO4 electrolyte was confirmed to have the highest specific capacitance of 412.94 F/g at a current of 1 A/g. Based on the results of this study, it is confirmed that cocoa pods have the potential to be a source of electrode base material with H2SO4 electrolyte solution as a source of charge carrier in supercapacitor cell devices.